2016
DOI: 10.1038/srep23494
|View full text |Cite
|
Sign up to set email alerts
|

Optical phase conjugation assisted scattering lens: variable focusing and 3D patterning

Abstract: Variable light focusing is the ability to flexibly select the focal distance of a lens. This feature presents technical challenges, but is significant for optical interrogation of three-dimensional objects. Numerous lens designs have been proposed to provide flexible light focusing, including zoom, fluid, and liquid-crystal lenses. Although these lenses are useful for macroscale applications, they have limited utility in micron-scale applications due to restricted modulation range and exacting requirements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Prominent examples include imaging through biological tissue or other highly scattering media such as fog, which distort incident wavefronts and hinder image formation. Some disordered media, however, can be used to enhance wavefront shaping capability, leveraging multiple scattering to expand both the spatial extent and range of wavevectors in an optical system [66][67][68][69][70][71][72]. In this case, the employed disordered medium must be fully characterized to understand its effect on an incident wavefront.…”
Section: Disorder-engineered Metasurfaces For Wavefront Shapingmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples include imaging through biological tissue or other highly scattering media such as fog, which distort incident wavefronts and hinder image formation. Some disordered media, however, can be used to enhance wavefront shaping capability, leveraging multiple scattering to expand both the spatial extent and range of wavevectors in an optical system [66][67][68][69][70][71][72]. In this case, the employed disordered medium must be fully characterized to understand its effect on an incident wavefront.…”
Section: Disorder-engineered Metasurfaces For Wavefront Shapingmentioning
confidence: 99%
“…In this case, the employed disordered medium must be fully characterized to understand its effect on an incident wavefront. In knowing the effect of the disordered medium, the distortion it introduces can be removed via post-processing or exploited in conjunction with a source to achieve more sophisticated functionalities [70][71][72][73]. Fig.…”
Section: Disorder-engineered Metasurfaces For Wavefront Shapingmentioning
confidence: 99%
“…An advantage of using the SLM as a wavefront corrector is the ability to generate an arbitrary pattern through the scattering layer [17,29]. To generate a 3d pattern, the phase often needs to be measured at different Z planes because of the limited axial FOV.…”
Section: D Multi-spot Patterningmentioning
confidence: 99%
“…The first demonstration of focusing through scattering media by Vellekoop et al [17] showed its potential for applications in fluorescent laser scanning microscopy. Several groups [23][24][25][26][27][28][29] further demonstrated the lateral or axial scanning of the focus behind the scattering layer utilizing the memory effect. Lateral scanning is realized by either rotating the beam around the scanning layers or by adding tip/tilt to the compensation phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation